The Effect of Animal Side Dish Modification "Rolade Ayam" on Acceptability in Adult Patients - Ria Fitria Madu; Purbowati Purbowati; Septiani Septiani (Indonesian Journal of Global Health Research, 2025)
Lack of food intake in inpatients or inpatients is often associated with adverse health consequences such as malnutrition. Nutrition services in the hospital's minimum service standards are determined to be at least 80% consumed by the patient. However, there are still many hospitals that have a percentage of leftover food that exceeds 20%. Food modifications are necessary to lower leftovers in hospitals and increase acceptability. The purpose of this study is to analyze the effect of animal side dish modification in the form of chicken rollade on patient acceptability. The research design in this study is a quasi-experimental or quasi-experimental with a One Group Pre-Post Test design.The research was conducted at the Fakfak Regency Regional General Hospital (RSUD) from June to July 2025. The sample in this study amounted to 43 adult patients were selected using purposive sampling. The protein menu modification used is chicken Rolade. While the pre test uses the previous menu, namely curry chicken. Acceptance assessment was carried out with a questionnaire on the related likert scale, taste, texture, and aroma. Analysis using the Paired T Test. The average acceptance score of curry chicken before menu modification was 3.11 (maximum score of 5). The average acceptance score of rolade chicken is 4.4. The results of the test showed a P value of <0.001. The chicken rolade menu is preferred and accepted by patients compared to the curry chicken menu.